Why Must Physicians Know About Oral Diseases? (2010)
Proper knowledge of oral diseases is crucial in medical practice due to the following reasons: (a) Periodontal disease is associated with multiple systemic conditions of medical interest, (b) a large number of systemic diseases have oral manifestations, (c) many drugs are associated with oral adverse drug reactions, (d) physicians are generally not sufficiently trained to detect oral cancer manifestations, (e) physicians could play a pivotal role in oral public health, and (f) early detection of oral diseases by physicians could improve the oral health status of the population.